Cetirizine-induced fixed drug eruption - Srija Gopal; Selvalaxmi Gnanasegaran; Gerard Marshall Raj; Sakthibalan Murugesan; Mangaiarkkarasi Adhimoolam (Journal of Research in Pharmacy Practice, 2018)
Cetirizine, a piperazine-derivative second-generation antihistaminic, is used for a wide variety of disorders such as urticaria, eczema, and allergies. Adverse reactions due to this drug are usually rare, especially fixed drug eruption (FDE), a delayed cell-mediated hypersensitivity reaction, is scarce. Here, we report a case of cetirizine-induced FDE. A 34-year-old female developed hyperpigmented, itchy patches over both forearms, legs, feet, and right side of the chest after taking tablet cetirizine for dry cough with similar episode 2 years back on the same sites. The patient responded slowly with conservative treatment and the lesions disappeared after 10 days. She was advised to avoid the causative in near future. This case report highlighted FDE due to an antihistaminic which themselves will be prescribed to treat allergies.